Thyroid Related Quality of Life in Elderly with Subclinical Hypothyroidism and Improvement on Levothyroxine is Distinct from that in Young Patients (TSAGE) - Recker, Stefanie; Voigtländer, Richard; Viehmann, Anja; Dunschen, Karin; Kerp, Helena; Frank-Raue, Karin; Leidig-Bruckner, Gudrun; Graf, Dieter; Lederbogen, Sebastian; Dietrich, Johannes W.; Görges, Rainer; Brabant, Georg; Völker, Uwe; Watt, Torquil; Zwanziger, Denise; Moeller, Lars Christian; Führer, Dagmar (Hormone and Metabolic Research, 2019)
The aim of this study was to investigate in a longitudinal approach whether levothyroxine (LT4) substitution has a different impact on quality of life (QoL) and thyroid related QoL in younger (<40 years) and older subjects (>60 years) with elevated thyroid-stimulating hormone (TSH) concentrations. The study included male and female patients with newly diagnosed, untreated subclinical hypothyroidism defined by TSH>8 mU/l. Patients were recruited throughout Germany from 2013–2016 and evaluated by clinical assessment, blood sampling and questionnaires for health related QoL and thyroid-disease thyroid-related QoL (ThyPRO) at time of diagnosis and six months after initiation of LT4 treatment. We found significantly lower QoL in both young and old patients with subclinical hypothyroidism compared to age-matched healthy individuals. Higher scores on follow-up were found in all patients irrespective of age, indicating better QoL on LT4 therapy. Analysis of the ThyPRO questionnaire showed that old patients experienced less Emotional Susceptibility, Tiredness, and Impaired Day Life on LT4, while young patients reported less Cognitive Complaints, Emotional Susceptibility, and Impaired Day Life compared to baseline assessment. Hypothyroidism with TSH concentrations>8 mU/l is associated with impairment in general and ThyPRO QoL in young and old age. Older patients benefited from LT4 therapy and remarkably show similar degree of improvement as younger patients, albeit with some thematic variation in ThyPRO QoL. Our data confirm current recommendations on initiation of LT4 substitution and suggest that this should not be withheld in elderly with TSH concentration above 8–10 mU/l.
Keywords: subclinical hypothyroidism; quality of life; aging; elderly; thyroid-stimulating hormone; levothyroxine treatment